Optimization of HPLC Using Central Composite Design for Determination of Curcumin and Demethoxycurcumin in Tablet Dosage Form - Siregar, Chairany; Prabaningdyah, Niken K; Choiri, Syaiful; Riyanto, Sugeng; Rohman, Abdul (Dhaka University Journal of Pharmaceutical Sciences, 2018)
In this study, central composite design (CCD) was used for optimization of high performance liquid chromatographic (HPLC) method for simultaneous analysis of curcumin (CUR) and demethoxycurcumin (DMC) in tablets containing Curcuma extract. Separation of CUR and DMC was performed using X-Bridge C18 column (250 x 4.6 mm i.d; 5 μm). Four factors that were investigated include the concentration of acetic acid (X1), ratio of acetic acid (X2), flow rate of mobile phase (X3) and column temperature (X4). Based on responses obtained (retention time, peak area, resolution and tailing factor), the optimum condition selected was X1 = 3.00%, X2 = 51%, X3 = 1.05 mL/min and X4 = 45oC. This HPLC condition was validated by assessing several validation parameters including system suitability test, selectivity, linearity, precision, accuracy and robustness according to International Conference Harmonization (ICH). All validation parameters meet the acceptance criteria set by ICH. The validated method was successfully used for analysis of CUR and DMC in tablets containing Curcuma extract. CCD was effective means in optimization of HPLC for analysis of CUR and DMC in pharmaceutical formulation. Dhaka Univ. J. Pharm. Sci. 16(2): 137-145, 2017 (December)